C36 ATRIAL SEPTAL DEFECT CLOSURE WITH A NEW OCCLUDER DEVICE, EXPERIENCE ON 100 PATIENTS. (18th May 2022) - Castaldi, B; Sirico, D; Di Candia, A; Cuman, M; Cantinotti, M; Di Salvo, G; Santoro, G
Abstract: Background: This perspective, observational study evaluated safety and efficacy of the GORE® Cardioform ASD Occluder (WL Gore & Associates, Flagstaff, AZ), compliant and potentially innovative prosthesis recently approved for closure of ostium secundum atrial septal defects (ASD). Methods: 100 unselected patients with significant ASD were submitted to trans–catheter closure with GORE® Cardioform ASD Occluder at two high–volume Italian Pediatric Cardiology centers. Primary endpoints were procedural success and safety. Secondary endpoints were closure rate and clinical safety at 1–month and 6–month follow–up. Results: Patients'age and weight were 7.8 (6.0–13.6)and 26.1 (20.0–54.0), respectively. ASD diameter was 17.4 + 4.4, resulting in QP/QS of 1.7 ± 0.7 (median 1.6). 33 patients presented an asd larger than 18mm in diameter. 58% of defects were considered complex based on the following characteristics: deficient rim(s) (except aortic rim), aneurismal/multi–fenestrated and ASD size/pt weight ratio >1.2. Device placement was successfully achieved in all but two patients (98%), in whom it embolized early after deployment, resulting in rescue surgical repair. No cross–over with different devices was recorded. Median procedure and fluoroscopy times were 54 and 11 min, respectively. Major adverse events were recorded in 7 pts. Complete closure rate was 87.3% at discharge, rising to 95.5% (39/42 pts) at 1 month evaluation, and 100% at 6 months without cardiac or extra–cardiac adverse events. "Complex" procedures were more time–consuming but as effective and safe as the "simple" ones. Conclusions: The GORE® Cardioform ASD Occluder device was highly effective and versatile in closure of ASDs with different anatomy and size, even in challenging settings.